3 Innovative four step bereavement service at a tertiary cancer centre. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Griffiths, Ann; Coackley, Alison; Cooper, Malcolm; Watson, Amanda; Benson, Sinead; Cadwallader, Claire; Monnery, Dan; Hampton-Matthews, Julian
Abstract : Background: Bereavement is defined as the state of a loss when someone close to you has died. It is important that people closely affected by a death are communicated with in a sensitive and timely manner and that those at risk of pathological bereavement reactions are identified and supported. At a tertiary cancer centre it was recognised that families need time and support soon after the death of their loved one. Aim: To deliver a 'day after death' service providing personalised bereavement support to families/carers and learn lessons about care by discussing their experiences. Methods: At our tertiary cancer centre we implemented an innovative 4 step approach to supporting bereaved families and carers: Comprehensive documentation including a bereavement risk assessment at the time of death. Innovative 'day after death' service. Post bereavement contact if accepted. Face to face follow up where required. The bereaved families/carers meet with a senior member of the Nursing Team who knew the patient on the next working day. They meet in a private room away from the wards and discuss how they are coping with their loss and listen to any questions/concerns they may have. The relevant paperwork is then provided. This also provides the opportunity to follow up the bereavement risk assessment undertaken by the ward staff. Following the meeting a reports is shared with the Director of Nursing and discussed at the Trust Executive meeting. Results: There have been 84 deaths within the tertiary cancer centre in the last 12 months. All bereaved families/carers have received the day after death service. This has enabled us to provide comprehensive and personalised bereavement care. It also enables us to identify those people likely to have complex bereavement and signpost to local specialist support services. Conclusions: We have successfully implemented a 4 step innovative service delivering personalised bereavement care.